The Environmental crisis--opposing viewpoints - Bernards, Neal, 1963- (San Diego, CA : Greenhaven Press, 1991)
Presents opposing views on questions of environmental protection and damage resulting from air and water pollution, toxic wastes, pesticides, and the ever-growing tide of refuse.
Includes bibliographical references and index.
Keywords: Environmental policy -- United States; Environmental protection